Stretching the Sociological Imagination
XXII, 277 p. 11 illus.
Keywords: This edited collection calls for renewed attention to the concept of the sociological imagination, allowing social scientists to link private issues to public troubles. Inspired by the eminent Glasgow-based sociologist, John Eldridge, it re-engages with the concept and shows how it can be applied to analyzing society today.